Elephantiasis and music - Jones, A. M. (International Library of African Music, 1972)
Just over a year ago I received a letter from someone I had never heard of - Dr. B. R. Laurence, Reader in Entomology at the London School of Hygiene and Tropical Medicine, University of London - saying he would like to meet me to discuss his findings arising out of his recent research. The present essay is the result of our meeting
Keywords: Elephantiasis; Ethnomusicology; Africa; Xylophone; Xylophone music; Musical instruments; African Music; Xylophone (Instrument)